Holding bankers to account a decade of market manipulation, regulatory failures and regulatory reforms - McDonald, Oonagh (Manchester scholarship online., 2019)
This book tells you all you need to know about the rigging of Libor, Forex and the Gold and Silver Fixes during and after the financial crisis of 2007-08.